Antioxidant Activity Determining Catechol Grouping Flavonol Glycosides from the Flowers of Aconitum hetrophyllum - Pappu Kumar; Chanyal Beena; Verma D. L. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Aconitum hetrophyllum (family, Ranunculaceae) is native to high reaches of Kumaun Himalaya. The extracts derived from the plant, Aconitum hetrophyllum have widely been used as a traditional medicines to cure diseases associate inflammations, cardiovascular, neuro-degenerative and other ailments, microbial, bronchitis and joint pains. Various biological activities, anti-inflammatory, anticarcerogenic, anti-spasmolytic and anti-microbial have been identified from the aqueous extracts of the plant. Although the principle biological active compound, aconite a ditertepenoid alkaloid and its various derivatives have previously been isolated from the plant. Recognizing an enormous traditional medicinal uses of the plant, the aqueous-methanolic extract derived from its flowers was investigated for antioxidative potential and activity bearing flavonol glycosides. The catechol-grouping flavonoids, a highly antioxidant active compounds, were isolated.